The utilization of ameliorant in formulation with a dose of different to improve the abudance fitoplankton in the media the peat soil. - Heri Anggoro; Syafriadiman '; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted from February to April 2016 in the ponds of peatsoils at Jl. Petani Nenas Desa Kualu Nenas, Tambang, Kampar, Riau. The observation have been done in Laboratory of Environment Quality Aquaculture (EQA), Fisheries and Marine Sciences Faculty, Riau University. Methods of experiment in this researchused with completely randomized design (CRD). Dose of ameliorant will be used as a factor in this research. 6 dose treatmentsare P0: without giving ameliorant, P1: 400 g / m2, P2: 600 g / m2, P3: 800 g / m2, P4: 1000 g / m2, P5: 1200 g / m2, and 3 replications. The results of this research that dose of ameliorant formulation a can increase the abudance fitoplankton. The best of treatment during thisresearch treatment of the P5 1200 g ameloirant + formulasi/ m2 and the fitoplankton abudance is 1954.6667 ind/l. further more this research result There 17 kinds of fitolankton, 6 species of cholorophyta, 7 speciescyanophyta, and 4 speciesbacillariophyta.Keywords: Ameliorant, Peat, and fitoplankton